Analysis the Mathematical Self-Concept of Children Aged 5-6 Years Old in Pekanbaru - Solfiah, Yeni; Kurnia, Rita (Proceedings of the UR International Conference on Educational Sciences, 2018)
Early childhood education is the foundation for further development. Because the concepts that children get at this level will be the basis for the next level of education. One important concept is mathematics. Various studies have revealed that children have difficulty learning the most basic concepts in daily life. Therefore, it is necessary to enrich what needs to be improved, so that children will not be afraid of learning mathematics. One of the determinants of ones success is from self-concept. When a child is playing and learning mathematics, the teacher should develop a childs self-concept of mathematics. The child will have high self-concept of mathematics. It will certainly affects the learning outcomes at the next level of education. This study tried to analyze the mathematical self-concept of children aged 5-6 years. The data collection technique is carried out by observing children while playing and learning in their preparation.Based on the research findings that carried out with quantitative descriptive methods obtained the mathematical self-concept of children aged 5-6 years in kindergarten FKIP University of Riau is categorizedinto average level. It is taken from the empirical average of 19.98. It showed 21 children or 50% are categorized into good level and the other 16 children or 38.10% are categorized into average level and 5 children or 11.90% are categorized into poor level.